URGENSI PERILAKU KOSUMTIF MENJADI BUDAYA TERHADAP MAHASISWA - Muhammad Putra Dinata Saragi; Ulfa Khairani; Aisyah Nurfathiyah; Meylin Hidayatullah; Ronauli Dania Siagian (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to explore, identify and relate the consumptive behavior experienced by students with their living cost (monthly allowance), lifestyle and conformity behavior. This research is a quantitative descriptive research. Where to find out the presentation of consumptive behavior of students who are still actively studying at their chosen university in continuing their studies. The steps taken in this research are collecting, classifying and analyzing or processing data, making conclusions and reports with the main aim of making an objective description of a situation in a description. The population used in this study, namely students who are still actively studying from various universities. The sample used was 100 students using the Probability Sampling technique. The measurement scale in this study uses a Likert scale. From the results of the study, there are several obstacles in its implementation but can be resolved properly. Students are expected to be smarter and more selective in spending money in purchasing an item, if the item is only of aesthetic value, it is better to think about it before buying it so that it can be used for other things in their daily needs.